Pelatihan dan Pendampingan untuk Pendirian Teaching Factory Sebagai Implementasi SDG’s 4: Training and Assistance for The Establisment of a Teaching Factory as Implementation of SDG’s 4 - Hermawan, Sigit; Rahmawati, Imelda Dian; Sriyono, Sriyono; Dini, Amelia Nugraha; Masrifah, Anis (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
There are two problems with partners, they do not yet have a teaching factory program that must exist in vocational schools or Vocational High Schools and networks with the Business World and the Industrial World (DUDI), which are still limited. Solution from the community services team namely training and assistance for establishing a teaching factory program. This is also the implementation of SDGs Number 4: the quality of education. The implementation method is observation, socialization, training, mentoring, and initiation to build networks for partners. Observations are carried out to obtain existing information. Teaching factory socialization and training is carried out by giving pre-tests and post-tests to participants. The result is increased participants' understanding of the teaching factory training material. Assistance has been carried out since the establishment of the teaching factory theme, namely taxation and computer accounting, determining the location of the internship at the Accounting and Tax Management Institute “Dharma Plus” Sidoarjo, and the launching of the teaching factory program. To increase the partnership with the Business World and the Industrial World, the community service team coordinated with KADIN Sidoarjo, and as a result, SMKN 2 Buduran Sidoarjo was invited to a meeting and met with KADIN Sidoarjo management. The output of this community service is that SMKN 2 Buduran already has a teaching factory program, "Taxation and Accounting Computers," and partnerships with member companies of the KADIN Sidoarjo and also a place for fieldwork practice of taxation, namely at the Accounting and Tax Management Institute “Dharma Plus” Sidoarjo.